2023
DOI: 10.1021/acs.jproteome.2c00578
|View full text |Cite
|
Sign up to set email alerts
|

Lipidomic and Metallomic Alteration of Caenorhabditis elegans after Acute and Chronic Manganese, Iron, and Zinc Exposure with a Link to Neurodegenerative Disorders

Abstract: Parkinson’s disease (PD) progresses with the loss of dopaminergic neurons in the substantia nigra pars compacta region of the brain. The superior mechanisms and the cause of this specific localized neurodegeneration is currently unknown. However, experimental evidence indicates a link between PD progression and reactive oxygen species with imbalanced metal homeostasis. Wild-type Caenorhabditis elegans exposed to redox-active metals was used as the model organism to study cellular response to imbalanced metal h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 69 publications
(113 reference statements)
0
1
0
Order By: Relevance
“…Acute exposure to iron and manganese and chronic exposure to zinc altered phospholipid composition, with an impact on the plasma membrane, changing also its fluidity and permeability; acute iron also significantly altered cardiolipins in the inner mitochondrial membrane. Thus, these authors showed lipidomic alterations as a consequence of altered metallostasis due to metal treatment [ 229 ].…”
Section: Lipidomics As a New Tool To Identify Biomarkers In Parkinson...mentioning
confidence: 99%
“…Acute exposure to iron and manganese and chronic exposure to zinc altered phospholipid composition, with an impact on the plasma membrane, changing also its fluidity and permeability; acute iron also significantly altered cardiolipins in the inner mitochondrial membrane. Thus, these authors showed lipidomic alterations as a consequence of altered metallostasis due to metal treatment [ 229 ].…”
Section: Lipidomics As a New Tool To Identify Biomarkers In Parkinson...mentioning
confidence: 99%